1985
DOI: 10.1103/physrevlett.55.280
|View full text |Cite
|
Sign up to set email alerts
|

Transfer cross sections for58Ni+58

Abstract: Transfer cross sections have been measured for 58 Ni + 58 ' 64 Ni in the energy range £ cm . = IOC-107 MeV with use of time of flight in a magnetic spectrograph. The direct reactions are dominated by one-neutron transfer, with other transfer cross sections being smaller by a factor of 3-4 or more. The average kinetic energy loss is -2 MeV. Over the measured energy range the total transfer cross section for 58 Ni + 58 Ni is smaller than that observed for 58 Ni + 64 Ni by a factor of 4.PACS numbers: 25.70.CdMuch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…We will show this in our magnetospectroscopic study [15]. Here we mention the Q-value spectrum measured by Rehm et al [50] for 64Ni(SaNi, 59Ni). In contrast to the CRC calculations of Esbensen et al [60] which were limited to states with Q > -3 MeV, the true experimental spectrum shows (despite the finite resolution) remarkable strength for Q < -3 MeV.…”
Section: Quasielastic Transfer Channels: Reflection From a Barrier Inmentioning
confidence: 91%
See 1 more Smart Citation
“…We will show this in our magnetospectroscopic study [15]. Here we mention the Q-value spectrum measured by Rehm et al [50] for 64Ni(SaNi, 59Ni). In contrast to the CRC calculations of Esbensen et al [60] which were limited to states with Q > -3 MeV, the true experimental spectrum shows (despite the finite resolution) remarkable strength for Q < -3 MeV.…”
Section: Quasielastic Transfer Channels: Reflection From a Barrier Inmentioning
confidence: 91%
“…This saturation seem to be generally reached (with some rest-fluctuations left, see later) for heavy systems, but not for light systems, where both very large (e.g. the Ni + Ni system [50,54]) and very low cross sections (e. g. the neutron pickup in the reaction 36S + 64Ni [55]) can occur. In the previous sections we have seen that the complex-channel reactions are able to explore the full multi-dimensional potential-energy surface of the merging dinuclear system, reseparating in part with total kinetic energies expected after a passage close to the conditional saddlepoint.…”
Section: Quasielastic Transfer Channels: Reflection From a Barrier Inmentioning
confidence: 96%
“…Its importance was first emphasized by Broglia et al [4,5] and the first indications were observed experimentally in transfer measurements of 58 Ni + 58,64 Ni [6]. A coupledchannels model of this effect was developed early on [7] in an attempt to make a consistent description of the fusion, transfer, and elastic scattering data that had been obtained in the 58 Ni + 64 Ni collisions.…”
Section: I Introductionmentioning
confidence: 99%
“…a=s 54. 8 The outgoing particles were momentum analyzed in the magnetic spectrograph ENMA and detected in the focal plane 13 opened 2.2° horizontally and vertically which corresponded to a solid angle of 1.6 msr. From a measurement of total energy E, energy loss SE, and position Bp an unambiguous determination of mass, atomic number, Q value, and atomic charge state q were possible.…”
mentioning
confidence: 99%